Assessing water- based recreational activities to project beach ecotourism potentials in Kisumu County - Ouma, Okungu Jared; Hayombe, Patrick O.; Agong', Stephen G. (IOSR Journal of Computer Engineering (IOSR-JCE), 2014)
This paper presents discussions on observed scenarios that characterize water-based recreational activities with an aim of laying grounds for appreciating relationships that enhance or hamper ecotourism development in Lake Victoria, Kisumu County. The study was premised from an argument that lake water resources demonstrate prospects for activities like swimming, boating, sunbathing, skiing, recreational fishing and visual amenities among others. The study was conducted through observations and confirmatory follow up queries from relevant stakeholders along Lake Victoria from Asat, Ogal, Usoma and Lwangni beaches of Lake Victoria. The main objective was to examine existing trends of water-based activities in relation to ecotourism and envisage potentials of each beach water front for recreation in Kisumu County. Thus, this paper presents results of a systematic synthesis of interactions between lake (surface) water and outdoor recreation, a significant socioeconomic subsystem. The study maps out characteristics of accessible water front areas, popularly known as beaches, for their ecological sensitivity and ascertains the possibility of the sites to be planned or augmented to facilitate ecotourism development. Findings reveal the spatial potential of the sites but with gaps that intimidate possible popularity of ecotourism industry due to intentional human activities, negligence and perceptions. The existing technical and scientific knowledge on Lake Victoria Basin has been boosted by this study; hence, results and recommendations potentially enable academic institutions, development agencies and Kisumu County Government to seriously begin ecotourism development, which has remained behind most developed nations
Keywords: Water-Based; Recreational Activities; Beach Ecotourism; Ecotourism Potential